2017
DOI: 10.1007/s13744-017-0518-y
|View full text |Cite
|
Sign up to set email alerts
|

Insects Associated with Pig Carrion in Two Environments of the Brazilian Savanna

Abstract: Studies of carrion fauna have increased in Brazil and have contributed to the knowledge of this fauna in the national territory. Brazil has continental dimensions and presents various biomes in its territorial area. Most of the carrion fauna have seldom been studied, and this is especially true for the Savanna or "Cerrado." The present research examined the fauna visiting carrion in two environments and two seasons in a rural area situated in a region of Cerrado in southeastern Brazil. The two environments stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
0
16
1
2
Order By: Relevance
“…Additional information obtained from screwworm adult captures contributed to providing a more complete distribution of C. hominivorax in the country ( Figure 2D, Table 2). Adults of C. hominivorax have been caught in several sites, mainly by traps baited with carcasses (ALVES et al, 2014;FARIA et al, 2018), rotting viscera or other decaying material (KOLLER et al, 2002(KOLLER et al, , 2011SOUSA et al, 2010;GONÇALVES et al, 2011;GADELHA et al, 2015;PEREIRA DE SOUSA et al, 2015OLIVEIRA et al, 2016). Although decaying baits are not the best attractant to a fly species causing primary myiasis, this relatively inexpensive and simple choice has provided useful information on the distribution of C. hominivorax in Brazil (Figure 2E).…”
Section: Adult Recordsmentioning
confidence: 99%
“…Additional information obtained from screwworm adult captures contributed to providing a more complete distribution of C. hominivorax in the country ( Figure 2D, Table 2). Adults of C. hominivorax have been caught in several sites, mainly by traps baited with carcasses (ALVES et al, 2014;FARIA et al, 2018), rotting viscera or other decaying material (KOLLER et al, 2002(KOLLER et al, , 2011SOUSA et al, 2010;GONÇALVES et al, 2011;GADELHA et al, 2015;PEREIRA DE SOUSA et al, 2015OLIVEIRA et al, 2016). Although decaying baits are not the best attractant to a fly species causing primary myiasis, this relatively inexpensive and simple choice has provided useful information on the distribution of C. hominivorax in Brazil (Figure 2E).…”
Section: Adult Recordsmentioning
confidence: 99%
“…Additionally, some studies found fly species and Camponotus visiting and feeding on animal carcasses in different regions of Brazil. The cooccurrence of flies and ants could give pseudoscorpions the opportunity to find new hosts or dispersal insects (Carvalho, Thyssen, Linhares, & Palhares, 2000;De Faria, Paseto, Couri, Mello-Patiu, & Mendes, 2017;Faria et al, 2013). Pseudoscorpions transported to carcasses on flies' bodies could locate new host ants and attach themselves to ant bodies to be transported to the colony or simply follow the ants returning to their colonies.…”
Section: Resultsmentioning
confidence: 99%
“…A riqueza e a abundância dos besouros podem variar de acordo com as condições climáticas e fisiogeográficas presentes em diferentes regiões, tornando-se assim relevante, para fins forenses, o conhecimento da entomofauna local (luederwaldT 1911;Pessôa & lane 1941;Marchiori et al 2000;Mise et al 2007Mise et al , 2008Mise et al , 2010rosa et al 2011;sanTos et al 2012;silva & sanTos 2012;Mayer & vasconcelos 2013;celli et al 2016;Faria et al 2017). Por esta razão, o objetivo deste estudo foi levantar a fauna local e registrar o comportamento sazonal de espécies de coleópteros associados a carcaças de roedor expostas em ambiente silvestre no município de Santa Maria, Rio Grande do Sul, Brasil, visando fomentar os bancos de dados de espécies de besouros para uso forense.…”
Section: E-issn 1983-0572unclassified
“…Embora Mayer & vasconcelos (2013) tenham registrado aproximadamente 96% das espécies com hábito necrófago, sanTos et al (2013) também relataram em seu estudo conduzido na caatinga um maior percentual de predadores, quando comparado às demais categorias ecológicas tais como onívoros, necrófagos ou coprófagos, sem, contudo notificar Carabidae. Faria et al (2017) A maior atratividade destes besouros nesta ocasião pode estar Tabela 2. Duração dos estágios de decomposição (em dias), dados abióticos (médias de temperatura, umidade relativa do ar e precipitação) e parâmetros ecológicos (diversidade, dominância e similaridade) para Coleoptera e as famílias mais abundantes por estação do ano.…”
Section: E-issn 1983-0572unclassified